Development and deployment of a pilot multilingual citizen- science mobile application for georeferenced marine catch observations in India - Dhanya M. Lal; T.N.C. Karthik; Sneha Jha; Chennuri Sathish; Susmita Raulo; R. Premkumar; Sanjiba Kumar Baliarsingh; Alakes Samanta; Sudheer Joseph; T.M. Balakrishnan Nair (Frontiers in Marine Science, 2026)
Marine fishery advisory services represent a translation of satellite-derived scientific information into actionable guidance for marine fishing communities in India, enabling fishers to locate potential fishing grounds more efficiently and reduce search time. To transform the advisories into forecasts and develop species-specific predictions of fishery grounds, high-quality and high-frequency georeferenced fish catch data over a large spatial scale is essential. To enhance data collection, INCOIS has developed a citizen science approach using a user-friendly Android App named ‘Fisheries Information Source Hub (FISH)’, enabling widespread citizen participation, mainly by the fishers using their mobile phones. This initiative simplifies data gathering and supports the long-term goal of reliable, species-specific fishery predictions. The data collected through the FISH App is transmitted to a central processing facility at INCOIS and undergoes necessary quality control before further analysis. This study introduces the FISH App, which has demonstrated encouraging outcomes during its initial deployment, with nearly a thousand installations and a 20-fold increase in data submissions between the first two years of implementation. The initiative holds significant potential for future development into a citizen science-based information hub, facilitating broader stakeholder participation and data-driven fisheries management.

In vitro activity of β-lactamase inhibitors avibactam, relebactam and vaborbactam in combination with aztreonam against metallo-β-lactamase producing Escherichia coli clinical isolates - Clément Viguier; Samanta Freire; Maxime Bouvier; Christophe Le Terrier; Laurent Poirel; A. Westers; M. Imperiali; L. Pozzi; D. Balzari; G. Vaninetti; C. Cirillo; V. Gaia; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Exploring the climate-driven dynamics of whitefly (Bemisia tabaci) Asia-I cryptic species population and their role in mungbean yellow mosaic India virus (MYMIV) transmission in black gram - Subham Dutta; Moumita Panda; Kousik Atta; Poorvasandhya R; Thomas Wilbur Davis; Ankur Mukhopadhyay; Souvik Samanta; Poly Saha; Jayanta Tarafdar; Mritunjoy Barman (Phytoparasitica, 2026)

Discussion: ‘Exploratory modelling of the impacts of sea-level rise on the Sundarbans mangrove forest, West Bengal, India’ by Samanta et al. (2023) Response to comment by Das and Bandyopadhyay (2025) Science of the Total Environment 972, 178937 - Sourav Samanta; Sugata Hazra; Jon R. French; Robert J. Nicholls; Partho P. Mondal (Science of The Total Environment, 2026)

Application of otolith morphology to unveil the stock structure of Hilsa shad (Tenualosa ilisha) in the Bhagirathi-Hooghly river system and the associated Northern Bay of Bengal - Sajina A.M.; Sangeetha M. Nair; Suresh V.V.R.; T. Maity; J. Mukherjee; S.K. Banik; Sandhya K.M.; R.K. Manna; R. Samanta (Regional Studies in Marine Science, 2025)

Methylocystis suflitae as a promising industrial workhorse for methane-based polyhydroxyalkanoate production - Eleni N. Moutsoglou; Dipayan Samanta; Tanvi Govil; Lee R. Krumholz; Christopher T. Garner; Rajesh K. Sani (Systems Microbiology and Biomanufacturing, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Recombinant 3AB3 nonstructural protein-based indirect ELISA for detection of foot-and-mouth disease virus infection-elicited antibodies in goat - M. Rout; L. K. Pandey; B. R. Prusty; R. Samanta; J. K. Mohapatra; R. P. Singh (Veterinary Research Communications, 2024)

Data processing of visible emission line coronagraph onboard ADITYA-L1 - Muthu Priyal; Jagdev Singh; B. Raghavendra Prasad; Chavali Sumana; Varun Kumar; Shalabh Mishra; S.N. Venkata; G. Sindhuja; K. Sasikumar Raja; Amit Kumar; Sanal krishnan; Bhavana S. Hegde; et al. (Advances in Space Research, 2024)

An integrated buoy-satellite based coastal water quality nowcasting system: India's pioneering efforts towards addressing UN ocean decade challenges - T.M. Balakrishnan Nair; V.V.S.S. Sarma; Aneesh A. Lotliker; K.R. Muraleedharan; Alakes Samanta; Sanjiba Kumar Baliarsingh; S. Shivaprasad; T.R. Gireeshkumar; Susmita Raulo; S.P. Vighneshwar; R Venkat Shesu; Murali Krishna; et al. (Journal of Environmental Management, 2024)

Exploratory modelling of the impacts of sea-level rise on the Sundarbans mangrove forest, West Bengal, India - Sourav Samanta; Sugata Hazra; Jon R. French; Robert J. Nicholls; Partho P. Mondal (Science of The Total Environment, 2023)

Geo-spatial distribution and trends of trawl catch and bycatch off the south Konkan coast, Maharashtra, India - Jaspreet Singh; A.K. Jaiswar; S.K. Ahirwal; Pranab Gogoi; U.R. Gurjar; R. Samanta; Kamal Sarma; Latha Shenoy (Regional Studies in Marine Science, 2023)

Statistical and geostatistical modelling approach for spatio-temporal assessment of river water quality: a case study from lower stretch of River Ganga - R. K. Raman; M. Bhor; R. K. Manna; S. Samanta; B. K. Das (Environment, Development and Sustainability, 2023)

Molecular characterization and serodiagnostic evaluation of the Echinococcus ortleppi recombinant glutaredoxin 1 protein for cystic echinococcosis in buffalo (Bubalus bubalis) - K.A. Yashica; S. Samanta; R. Balaji; V. Jawalagatti; M. Silamparasan; S. Anandu; A. Rialch; S.C. Gupta; Anup Kumar Tewari (Veterinary Parasitology, 2023)

Detection and in silico characterization of banana bunchy top virus in West Bengal, India: relevance to global genetic diversity and population structure - Swati Chakraborty; Subham Dutta; Mritunjoy Barman; Snigdha Samanta; Krishna Pada Sarkar; R. Poorvasandhya; Jayanta Tarafdar (VirusDisease, 2023)

Antibacterial effect of kitchen herbs against pathogenic multidrug-resistant E. coli isolates from calf diarrhoea - Saroj Rai; M. Kumar; R. Jas; G. P. Mandal; I. Samanta; M. Rajendar; S. Tripura; S. K. Das; M. Mondal; D. K. Mandal (Tropical Animal Health and Production, 2023)

Assessment of Spatial and Temporal Changes in Water Quality of a Tropical River in Southern Western Ghats, Kerala, India, Using Physicochemical Quality Indices and Multivariate Analysis - Ajoy Saha; T. T. Paul; Deepa Sudheesan; Sravan Kumar Sharma; V. R. Suresh; B. K. Das; S. Manoharan; M. E. Vijaykumar; S. Samanta; Chayna Jana (Natural Resources Research, 2022)

Did the Coronavirus Disease 2019 Lockdown Phase Influence Coastal Water Quality Parameters off Major Indian Cities and River Basins? - Aneesh Anandrao Lotliker; Sanjiba Kumar Baliarsingh; R. Venkat Shesu; Alakes Samanta; R. Chandrasekhar Naik; T. M. Balakrishnan Nair (Frontiers in Marine Science, 2021)
The end of the current decade experienced an outbreak of a new strain of coronavirus classified as severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) [coronavirus disease 2019 (COVID-19)] that spread across the globe within a short span of time and was declared as a global pandemic by the World Health Organization. In order to contain the spread of COVID-19, the Indian Government imposed lockdown in various phases, namely, the strict lockdown period (SLP) and relaxed lockdown period (RLP). The present study addresses changes in the magnitude of satellite-derived water quality parameters in the coastal waters off major Indian cities (Mumbai and Chennai) and river basins (Narmada, Mandovi-Zuari, Netravathi, Periyar, Kaveri, Krishna-Godavari, Mahanadi, and Hooghly) along the eastern Arabian Sea (EAS) and western Bay of Bengal (WBoB) during SLP and RLP. The daily climatology (2003–2019) and anomaly (2020) of different water quality parameters, viz ., chlorophyll- a (chl- a ), downwelling diffused attenuation coefficient (k d 490), and particulate organic carbon (POC) were used in the present study to eliminate seasonal biases and to unravel the signature of lockdown-induced changes in the magnitude of the above water quality parameters. During the total lockdown period, the magnitude of the above parameters reduced significantly in the coastal waters of both the EAS and the WBoB. However, this reduction was more significant in the coastal waters of the WBoB, attributed to a reduction in the supply of anthropogenic nutrients. Among different studied locations, the magnitude of water quality parameters significantly decreased off Chennai and Hooghly, during SLP, which subsequently increased during RLP probably due to reduction in anthropogenic material influx during SLP and increase during RLP. During RLP, the coastal waters off Mahanadi showed a maximum decrease in the magnitude of water quality parameters followed by Mandovi-Zuari, irrespective of these regions’ quantum of anthropogenic material input, possibly due to the higher response time of the ecosystem to reflect the reduction in anthropogenic perturbations. The satellite-retrieved water quality parameters have provided valuable insight to efficiently describe the changes in the health of the Indian coastal environment in terms of phytoplankton biomass and water clarity.

Waste Cooking (Palm) Oil as an Economical Source of Biodiesel Production for Alternative Green Fuel and Efficient Lubricant - Suprakash Samanta; Rashmi R. Sahoo (BioEnergy Research, 2021)

Metal contaminations in sediment and associated ecological risk assessment of river Mahanadi, India - S. Samanta; Vikas Kumar; S. K. Nag; R. K. Raman; K. Saha; S. Bandyopadhyay; B. P. Mohanty; B. K. Das (Environmental Monitoring and Assessment, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Status of Hilsa Fishery in Hooghly-Bhagirathi River System and Associated Coastal Waters of Northern Bay of Bengal - A. M. Sajina; V. R. Suresh; K. M. Sandhya; J. Mukherjee; R. K. Manna; B. K. Behera; R. Samanta; T. Maity; S. K. Banik (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

A First Global Oceanic Compilation of Observational Dissolved Aluminum Data With Regional Statistical Data Treatment - Jan-Lukas Menzel Barraqueta; Saumik Samanta; Eric P. Achterberg; Andrew R. Bowie; Peter Croot; Ryan Cloete; Tara De Jongh; Maria D. Gelado-Caballero; Jessica K. Klar; Rob Middag; Jean C. Loock; Tomas A. Remenyi; et al. (Frontiers in Marine Science, 2020)

Assessment of adverse impacts of glyphosate-based herbicide, Excel Mera 71 by integrating multi-level biomarker responses in fishes - P. Samanta; S. Pal; A. K. Mukherjee; T. Senapati; J. Jung; A. R. Ghosh (International Journal of Environmental Science and Technology, 2019)

Uses for humanised mouse models in precision medicine for neurodegenerative disease - Remya R. Nair; Silvia Corrochano; Samanta Gasco; Charlotte Tibbit; David Thompson; Cheryl Maduro; Zeinab Ali; Pietro Fratta; Abraham Acevedo Arozena; Thomas J. Cunningham; Elizabeth M. C. Fisher (Mammalian Genome, 2019)
Neurodegenerative disease encompasses a wide range of disorders afflicting the central and peripheral nervous systems and is a major unmet biomedical need of our time. There are very limited treatments, and no cures, for most of these diseases, including Alzheimer’s Disease, Parkinson's Disease, Huntington Disease, and Motor Neuron Diseases. Mouse and other animal models provide hope by analysing them to understand pathogenic mechanisms, to identify drug targets, and to develop gene therapies and stem cell therapies. However, despite many decades of research, virtually no new treatments have reached the clinic. Increasingly, it is apparent that human heterogeneity within clinically defined neurodegenerative disorders, and between patients with the same genetic mutations, significantly impacts disease presentation and, potentially, therapeutic efficacy. Therefore, stratifying patients according to genetics, lifestyle, disease presentation, ethnicity, and other parameters may hold the key to bringing effective therapies from the bench to the clinic. Here, we discuss genetic and cellular humanised mouse models, and how they help in defining the genetic and environmental parameters associated with neurodegenerative disease, and so help in developing effective precision medicine strategies for future healthcare.

Spatial distribution and potential biological risk of some metals in relation to granulometric content in core sediments from Chilika Lake, India - Saroja K. Barik; Pradipta R. Muduli; Bita Mohanty; Prasanta Rath; Srikanta Samanta (Environmental Science and Pollution Research, 2018)

Trace metal concentrations in euryhaline fish species from Chilika lagoon: human health risk assessment - S. Parida; S. K. Barik; B. Mohanty; P. R. Muduli; S. K. Mohanty; S. Samanta; A. K. Pattanaik (International Journal of Environmental Science and Technology, 2017)

Sero-detection of Toxocara canis infection in human with T.canis recombinant arginine kinase, cathepsin L-1 and TES-26 antigens - Anju Varghese; Opinder K. Raina; Dinesh Chandra; Bijay R. Mirdha; Naresh H. Kelawala; Jayesh B. Solanki; Niranjan Kumar; Reghu Ravindran; Anandanarayanan Arun; Ajayta Rialch; Hniang Lalrinkima; Rohan N. Kelawala; et al. (Acta Parasitologica, 2017)
Three recombinant antigens

Guanosine Anxiolytic-Like Effect Involves Adenosinergic and Glutamatergic Neurotransmitter Systems - Roberto Farina Almeida; Daniel Diniz Comasseto; Denise Barbosa Ramos; Gisele Hansel; Eduardo R. Zimmer; Samanta Oliveira Loureiro; Marcelo Ganzella; Diogo Onofre Souza (Molecular Neurobiology, 2017)

Experimental Lung Injury Promotes Changes in Oxidative/Nitrative Status and Inflammatory Markers in Cerebral Cortex of Rats - Maira J. da Cunha; Aline A. da Cunha; Samanta O. Loureiro; Fernanda R. Machado; Felipe Schmitz; Janaína Kolling; Eduardo P. Marques; Angela T. S. Wyse (Molecular Neurobiology, 2015)

ESBL-producing Shiga-toxigenic E. coli (STEC) associated with piglet diarrhoea in India - Rajkumari Mandakini; Tapan Kumar Dutta; Santhalembi Chingtham; Parimal Roychoudhury; Indranil Samanta; Sidhartha Narayan Joardar; Abigail R. Pachauau; Rajesh Chandra (Tropical Animal Health and Production, 2015)

Mild Hyperhomocysteinemia Increases Brain Acetylcholinesterase and Proinflammatory Cytokine Levels in Different Tissues - Emilene B. S. Scherer; Samanta O. Loureiro; Fernanda C. Vuaden; Aline A. da Cunha; Felipe Schmitz; Janaína Kolling; Luiz Eduardo B. Savio; Maurício R. Bogo; Carla D. Bonan; Carlos A. Netto; Angela T. S. Wyse (Molecular Neurobiology, 2014)

Identification of MDP (muramyl dipeptide)-binding key domains in NOD2 (nucleotide-binding and oligomerization domain-2) receptor of Labeo rohita - Jitendra Maharana; Banikalyan Swain; Bikash R. Sahoo; Manas R. Dikhit; Madhubanti Basu; Abhijit S. Mahapatra; Pallipuram Jayasankar; Mrinal Samanta (Fish Physiology and Biochemistry, 2013)

Mild hyperhomocysteinemia reduces the activity and immunocontent, but does not alter the gene expression, of catalytic α subunits of cerebral Na+,K+-ATPase - Emilene B. S. Scherer; Samanta O. Loureiro; Fernanda C. Vuaden; Felipe Schmitz; Janaína Kolling; Cassiana Siebert; Luiz Eduardo B. Savio; Bruna M. Schweinberger; Maurício R. Bogo; Carla D. Bonan; Angela T. S. Wyse (Molecular and Cellular Biochemistry, 2013)

Induction of toll-like receptor (TLR) 2, and MyD88-dependent TLR- signaling in response to ligand stimulation and bacterial infections in the Indian major carp, mrigal (Cirrhinus mrigala) - Madhubanti Basu; Banikalyan Swain; Bikash R. Sahoo; Nikhil K. Maiti; Mrinal Samanta (Molecular Biology Reports, 2012)

Analytical improvements of hybrid LC-MS/MS techniques for the efficient evaluation of emerging contaminants in river waters: a case study of the Henares River (Madrid, Spain) - Andrés Pérez-Parada; María del Mar Gómez-Ramos; María Jesús Martínez Bueno; Samanta Uclés; Ana Uclés; Amadeo R. Fernández-Alba (Environmental Science and Pollution Research, 2012)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Photochemical Transformation of the Fungicide Chlorothalonil by Ultra Violet Radiation - S. Samanta; R. K. Kole; L. K. Ganguly; A. Chowdhury (Bulletin of Environmental Contamination and Toxicology, 1997)